Trends in laboratory detection of Burkholderia pseudomallei and their antibiotic susceptibility pattern from clinical samples over twenty one years from 2001 to 2021 in a tertiary care hospital of Bangladesh (Bangladesh Journal of Medical Microbiology, 2021)
Melioidosis, a highly fatal infectious disease caused by Burkholderia pseudomallei, is largely under-recognized and underreported due to lack of alertness of health care professionals. The real burden of melioidosis in our country is poorly understood. Here, we have documented laboratory isolation trends of B. pseudomallei from different clinical samples sent to our Microbiology department from 2001 to 2021, with the aim to increase awareness among clinicians and microbiologists in the health care community of Bangladesh. A total of 86 B. pseudomallei, isolated from culture of different clinical samples in 68 melioidosis cases were studied retrospectively from hospital records. Antimicrobial susceptibility result by Kirby Bauer disk diffusion method was also analyzed. The most commonly affected age group was 46-60 years and majority of them (88.2%) had diabetes mellitus. Septicaemia (51.5%) was the most common presentation followed by skin and subcutaneous tissue abscess (29.4%), septic arthritis (16.2%), UTI (13.2%), pneumonia (10.3%), visceral abscess in lung (5.9%), liver (5.9%), spleen (7.3%) etc and death was reported among 32.5% cases. One case of laboratory acquired melioidosis was diagnosed from cleaner of our Microbiology laboratory. Average isolation rate of B. pseudomallei was 5.6 per year in our centre. The organism was isolated most frequently from blood (40.7%) and pus/wound swab (30.2%) samples. All the isolates were highly sensitive (>95%) to ceftazidime, carbapenem, piperacillin-tazobactum, amoxicillin-clavulanic acid and tetracycline, but 53.4% and 67.2% of our strains were recorded sensitive to co-trimoxazole and ciprofloxacin by disc diffusion method. In conclusion, melioidosis might be included as notifiable disease in national surveillance system of Bangladesh to provide key part in priority-setting, planning, also monitoring and evaluation of the disease control programs. Prompt early diagnosis and appropriate antibiotic administration are the critical steps to prevent mortality and morbidity from this deadly disease.Bangladesh J Med Microbiol 2021; 15 (1): 8-14